Adorning Holika effigy with all the markers of a married woman - Mumbai Archive Project Team (Jio Institute, 2024)
Married women in the family adorn Holika with all the visual markers of a married woman. This includes items of solah shringar, which comprise 16 pieces of jewellery and accessories that complete the traditional look of a Hindu bride, placed on the effigy.